2023
DOI: 10.3390/jcm12041675
|View full text |Cite
|
Sign up to set email alerts
|

Risankizumab Therapy for Moderate-to-Severe Psoriasis—A Multi-Center, Long-Term, Real-Life Study from Poland

Abstract: The present multi-center, long-term, real-life study made an attempt to assess the efficacy of risankizumab in the treatment of moderate-to-severe plaque psoriasis. The study comprised 185 patients from 10 Polish dermatologic departments undergoing risankizumab treatment. The disease severity was measured using the Psoriasis Area and Severity Index (PASI) before the start of the risankizumab treatment and next at the defined timepoints, i.e., 4, 16, 28, 40, 52 and 96 weeks of treatment. The percentage of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
2
5
2
Order By: Relevance
“…Similar effectiveness, regardless of BMI, has also been observed for the other two IL-23 inhibitors [20,21]. However, the presence of at least one CMD in our study was a predictor of lower response to the treatment at weeks 16, 28, 52, and 104, with comparable results to those observed by Adamczyk et al [22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar effectiveness, regardless of BMI, has also been observed for the other two IL-23 inhibitors [20,21]. However, the presence of at least one CMD in our study was a predictor of lower response to the treatment at weeks 16, 28, 52, and 104, with comparable results to those observed by Adamczyk et al [22].…”
Section: Discussionsupporting
confidence: 91%
“…In the multivariate analysis, the involvement of difficult-to-treat areas was associated with lower effectiveness in the short term, as expected. However, from week 52 onwards, these differences were no longer recorded, except for PASI100 at week 52, which could be explained by a minimal residual PASI in these areas [13,19,22]. In our study, risankizumab was rapidly effective, particularly in patients with genital psoriasis, which improved patient well-being [23].…”
Section: Discussioncontrasting
confidence: 47%
“…Te current real-life literature only partially aligns with our fndings. Several real-life studies have reported that BMI, psoriatic arthritis, and previous biologic failure may be associated with a reduced treatment response [7,[14][15][16]. In contrast, other studies did not fnd this correlation [8,17,18], which confrms our data and suggests that risankizumab could be used also in special categories of patients with unfavorable characteristics, such as obese, multitreated ones, or those with very severe disease.…”
Section: Discussionsupporting
confidence: 60%
“…Tese data have been confrmed by several real-world studies [5,6]. However, the majority of these reports described the short-term efectiveness of risankizumab, and to date, data about the long term are scarce [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…7 In our experience, the bio-naive status was independently associated with better responses throughout the study period, consistent with other experiences on IL-23 inhibitors. [8][9][10] This study has a few limitations, being its retrospective nature and the heterogeneity of clinical evaluations from different clinicians. However, its main strengths are the large sample size and the extended follow-up, along with the analysis of the subpopulations of patients with a recent history of psoriasis.…”
mentioning
confidence: 99%